Silicon acquisition and accumulation in plant and its significance for agriculture - Guo-chao YAN; Miroslav Nikolic; Mu-jun YE; Zhuo-xi XIAO; Yong-chao LIANG (Journal of Integrative Agriculture, 2018)
Although silicon (Si) is ubiquitous in soil and plant, evidence is still lacking that Si is essential for higher plants. However, it has been well documented that Si is beneficial for healthy growth of many plant species. Si can promote plant mechanical strength, light interception, as well as resistance to various forms of abiotic and biotic stress, thus improving both yield and quality. Indeed, application of Si fertilizer is a rather common agricultural practice in many countries and regions. As the beneficial effects provided by Si are closely correlated with Si accumulation level in plant, elucidating the possible mechanisms of Si uptake and transport in plants is extremely important to utilize the Si-induced beneficial effects in plants. Recently, rapid progress has been made in unveiling molecular mechanisms of Si uptake and transport in plants. Based on the cooperation of Si influx channels and efflux transporters, a model to decipher Si uptake, transport and distribution system in higher plants has been developed, which involves uptake and radial transport in root, xylem and inter-vascular transport and xylem unloading and deposition in leaf. In this paper, we overviewed the updated knowledge concerning Si uptake, transport and accumulation and its significance for the major crops of agricultural importance and highlighted the further research needs as well.